Pengaruh Solvabilitas, Likuiditas, dan Profitabilitas terhadap Nilai Perusahaan - Prasetyo, Yoyok; Ernawati, Nani; Hakim, Ahmad M Ryad S; Sugianto, Deris (Jurusan Akuntansi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Pekalongan, 2021)
Corporate Value Is the investor's perception of the level of success of the company which is reflected in the stock price. The higher the value of the company, the greater the prosperity received by shareholders. This study aims to determine the effect of Solvency, Liquidity and Profitability on the Company Value of the property and real estate sector listed on the Indonesia Stock Exchange in the 2015-2019 Period. The population in this study are property and real estate sector companies listed on the Indonesia Stock Exchange in the 2015-2019 period, amounting to 75 companies. Based on the sampling technique with purposive sampling obtained a sample of 16 companies. Data collection techniques use the documentation of financial statements published on the official website of the Indonesia Stock Exchange, www.idx.co.id. The analysis technique used is panel regression. The results of this study indicate that: (1) Solvency is not impacted on firm value, with a significance value of 0,1008>0.05 (2) Liquidity is not impacted on Firm Value, with a significance of 0,5810>0.05 (3) Profitability is not impacted on Firm Value, with significance of 0,3354>0.05 (4) Solvency, Liquidity, and Profitability affect the Value of the Company with a probability of 0,000 with an R2 of 85,90%.